Pressure-Related Universal Previtreous Behavior of the Structural Relaxation Time and Apparent Fragility - Drozd-Rzoska, Aleksandra (Frontiers in Materials, 2019)
The report presents the evidence for the ‘universal’ previtreous behavior of the reciprocal of the pressure related apparent fragility. This finding was the base for deriving the ‘model-free’ dependence for the pressure evolution of the structural relaxation time. All these led to new conclusions for the dynamic crossover phenomenon. Finally, the behavior of electric conductivity in the previtreous domain is discussed. The experimental evidence covers 8*OCB (liquid crystal), EPON 828 (resin) and diisobutyl phthalate, propylene carbonate (low molecular weight liquids). Experiments were carried up to extreme P 2.2 GPa, in the ‘bulk’ measurement capacitor. The report contains a summary of applied so far descriptions for the pressure evolution of dynamic properties on approaching the glass transition.